Ratusan IUP Mati Menimbulkan Masalah Legalitas (Studi Kasus Di Kalimantan Timur) - Munif, Abdul (Universitas 17 Agustus 1945 Samarinda, 2016)
This research will know the illegal mining action in some local government in East Government in 2014. The method of it is qualitative one and the data are taken from the newspaper and observation as well as interview. The results of this research are (1). The are many mining company have no legal permit, (2). There are many inspired permit, (3). There are many companies have complains because the coal robbing in the tugboat in the river Mahakam, (4). There are many illegal funding in the business, (5). The lead officers in Samarinda based on the regulation No. 23 in the year 2014 about Local government there is no technical and realization handbook, (6). The officers concerned are afraid to take an action to capture the robbers becuase no instruction. The suggestions are: (1). Samarinda local government has to proactive, (2). Good Governance has to be practised, (3). The officers have to burn down the crime, (4). The one who will urged the wants must be taken an action strictly to capture or sentence, (5). The society has to anticipate to create order and safe.